Atribut Local Genius Karya Video Bayu Skak - Gunawan Susilo (LPPM STIKI Malang, 2024)
Communication technologies are developing very quickly, especially Internet-based communications. This corresponds to the evolution of the existing social situation, in particular the use of social networks, which is also growing rapidly. The video site YouTube is an example. Even the use of internet technology has penetrated the business world (industry). The popularity of YouTube social networks encourages users (YouTubers) to use this application or social networks to promote themselves. Bayu Skak is a YouTuber who has successfully established his presence in the video media and has now even appeared on the big screen and television. The main purpose of the qualitative descriptive research is to provide an in-depth description of Bayu Skak's video works, both visual and sound. This study adopts a qualitative descriptive approach. The results of the study show that Bayu Skak's videos on the YouTube channel are an expression of the popularity of the social network YouTube, which provides space for expression. The expression space of YouTubers cannot be separated from industrial packaging, which can combine expression and economy. Bayu Skak uses this space of expression to give his work a strong local genius identity, including the use of East Javanese vocabulary and dialect in his work